Individual Development in Increasing Teacher Professionalism at SMA Negeri 1 Cirebon City - Suklani Suklani; Imam Sibaweh (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This research aims to determine the picture of teacher professionalism at SMA Negeri 1 Cirebon City. Teacher professionalism requires individual development and organizational development. One of the individual developments is carrying out professional teacher education and training. This improvement requires teacher expertise in educating and teaching students with various approaches and learning models. The research used quantitative descriptive analysis methods on 16 teachers as respondents at SMA Negeri 1 Cirebon City and interviews to ensure the validity of the instrument answers distributed through the survey. Data collection techniques were carried out using observation and survey instruments. The results of the research show that the development of teacher professionalism has four aspects, namely: the development of teacher professionalism for 16 teachers at SMA Negeri 1 Cirebon City has four aspects, namely: (1) expertise, including (a) mastery of the material ( 37.5% ) ( b) class mastery (31.255%), and (c) pedagogical mastery (31.25%), (2) sources of income, including: (a) meeting basic family needs (62%), (b) being able to share with others (25%), and (c) not lacking financially (12.5%), (3) improving quality, including: (a) increasing student achievement (50%), (b) increasing school achievement (31.25% ), and (c) increasing personal achievement (18.75%), and (4) code of ethics, including (a) maintaining integrity (100%), (b) honesty (100%), (c) discipline (100 %), and (d) responsible (100%). Teacher professionalism development must be carried out periodically and continuously.